Student counseling with nursing students from Universidad del Valle: Search, meeting, permanent challenge (Colombia Medica, 2024)
Introduction:  The issue of student counseling, as all the issues involved in a comprehensive higher education perspective, includes irresolvable tensions which are always enlightening in discovering the answer to the question: what kind of human beings are formed in the university and what kind of society is going to be built with them? The search for the answer to this question has meaning and matters to all instances and participants in the educational community.Student counseling, comprehensive education, and human care: The practice of Student Counseling includes opportunities for personal and professional growth, along with social projection of students and faculty. For the institution and its academic programs, it constitutes a field for the concrete appplication of the principles and goals of what «ought to be» according to the institutional mission at both levels. In caring for the «other», it is essential to know who that other is. Student Counseling in the School of Nursing at Universidad del Valle has been based on this premise. Its practice has demanded and enhanced knowing the students, their original contexts, expectations, concerns, and difficulties plus their human and professional potentials. The reflections presented here include facts and voices, learnings and processes, limits and scopes of this experience, seeking to recall a memory that demands a place and to contribute to the discussion, fortunately ever-present, about the student as the center and sense of every educational process.